(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The research deals with the term of adjustment of conduct that aims to guarantee the rights of the personality, in particular, collective and diffuse rights. It considers the term of adjustment of conduct an instrument that overcomes the slowness of the Brazilian Judiciary, representing a way that can bring efficiency in the reparation of violated rights and present a solution to correct conducts that are in disagreement with the law. From a critical perspective, it aims to show that the difficulty of the conduct adjustment term is that it can be breached, however, it seeks a negotiation that can guarantee a more beneficial result in favor of the public interest. The deductive method was used, searching for information in books, scientific articles and other documents that were suitable for the development of the research. The results suggest that the conduct adjustment term is a faster and more effective measure to guarantee diffuse and collective rights and, thus, the personality rights of consumers affected by irregular conduct.